(Invited) Use of E-ALD by SLRR of Cu UPD Layers for the Growth of Pd Thin Films in One-Cell Configuration. (26th March 2018) - Achari, Innocent; Ambrozik, Stephen; Dimitrov, Nikolay
Abstract : This work illustrates the application of electrochemical atomic layer deposition (E-ALD) by surface limited redox replacement (SLRR) in one-cell configuration for the growth of Pd thin films using underpotentially deposited Cu (CuUPD ) as a sacrificial metal. The growth of Pd films on Au was monitored by open circuit chronopotentiometry while the roughness evolution and thickness of accordingly deposited Pd films were assessed by HUPD and CuUPD cyclic voltammetry and stripping experiments, respectively. The growth of smooth Pd films was observed for about 15 equivalent monolayers (MLs) of Pd followed by a rapid transition to dendritic growth. A comparison with counterpart results of Pd SLRR deposition in a flow-cell suggests that the dendritic growth in one-cell is associated with establishment of mass-transport limitations. To address this shortcoming a modified protocol introducing SLRR-cycle disruption and forced convection was applied to demonstrate the growth of 26 MLs thick, smooth and continuous Pd film.